An analysis of the psychiatric treatment efficiency for alcohol use disorder: An integrative review - Almeida, Alexandro Barreto; de Morais, Davi Medeiros; Matsunaga, Marcela Aya Coelho (Seven Editora, 2023)
Alcohol addiction has been a problem in Brazil and it tends to get worse even more, the high consumption of alcohol can lead to many diseases, some are acute diseases and chronic disorders. There are many methods to treat these people and reduce the consumption of alcohol, one of the methods is the use of drugs which inhibits the desire for alcohol. For this reason, this integrative review has the objective of reviewing the efficacy of the psychiatric treatment of alcohol dependency with the drugs naltrexone, disulfiram and acamprosate. This integrative review was made with data from: US National Library of Medicine (PubMed); Scientific Electronic Library Online (SciElo). The final sample was 18 articles; The results show that the psychiatric treatment of the alcohol dependency with the studied drugs (naltrexone, disulfiram and acamprosate) have been shown to be effective. DOI: https://doi.org/10.56238/methofocusinterv1-108